Helping behavior and its relation with the temperament styles of university students - Koodi, Aseel K.; Hamzah, Farhan M. (Al-Adab Journal, 2020)
The research aimed at identifying the relationship of help behavior with mood methods. It was applied to a sample of 376 students from Al-Mustansiriya University using the aid behavior scale that was built for the purposes of the current research and the Quercy Scale (1978) to measure mood methods. In its results, the research found that the level of auxiliary behavior among students increased and male students had a higher level than female students. It also found that there is a high percentage of extraverted students compared to introverted students, And the presence of a high proportion of sensory students compared to intuitive students, and the presence of a high proportion of thinking students compared to emotional students, and the presence of a high proportion of cognitive students compared to students with the provision of judgment. The relationship was a statistical function between auxiliary behavior and extroversion and introversion, and not a statistical function with the removal of other moods. The results showed that there were differences between male and female students in the relationship of help behavior with two mood styles (extrovert and introvert), as students were more extroverted than female students and were less introverted than them. There were also differences between male and female students in the relationship of help behavior to the two ways of thinking and giving judgment, The relationship was a statistical function between auxiliary behavior and extroversion and introversion, and not a statistical function with the dimensions of other moods. The results showed that there were differences between male and female students in the relationship of help behavior with two mood styles (extrovert and introvert), as students were more extroverted than female students and were less introverted than them. There were also differences between male and female students in the relationship of help behavior with the two ways of thinking and giving judgment, if the relationship between students is higher than it is among female students, while the results showed that the relationship between help behavior and giving judgment is higher for female students than they are among students. There are differences in the relationship between help behavior and other moods.